First-Generation Students in Distance Education Program: Family Resources and Academic Outcomes - Brubacher, Michael R.; Silinda, Fortunate T. (International Review of Research in Open and Distributed Learning, 2021)
Distance education students have less access to classmates as a social resource and may, therefore, rely more on family members for support. However, first-generation students, or students who are the first in their family to attend university, may lack the academic resources that family members can provide. Overall, first-generation students in distance education programs may be at particular risk of lacking the necessary social capital to thrive in university. This study investigated whether two family resource variables—providing guidance about university and expressing supportive attitudes toward university—varied across generation status among distance education students. The study also investigated whether these family resource variables predicted students’ academic adjustment and academic persistence. A sample of 224 undergraduate, distance education students in South Africa completed an online survey. First-generation students (n = 60) reported receiving less university guidance from family members compared to continuing-generation students. In addition, receiving university guidance predicted students’ academic adjustment. The results suggest that university guidance from family members may serve as a protective factor against potential challenges that can impact students’ academic adjustment, a protective factor that first-generation students are less likely to have.